CaMKII activation participates in doxorubicin cardiotoxicity and is attenuated by moderate GRP78 overexpression - Tscheschner, Henrike; Meinhardt, Eric; Schlegel, Philipp; Jungmann, Andreas; Lehmann, Lorenz; Müller, Oliver J.; Most, Patrick; Katus, Hugo; Raake, Philip (PLOS ONE, 2019)
The clinical use of the chemotherapeutic doxorubicin (Dox) is limited by cardiotoxic side-effects. One of the early Dox effects is induction of a sarcoplasmic reticulum (SR) Ca2+ leak. The chaperone Glucose regulated protein 78 (GRP78) is important for Ca2+ homeostasis in the endoplasmic reticulum (ER)—the organelle corresponding to the SR in non-cardiomyocytes—and has been shown to convey resistance to Dox in certain tumors. Our aim was to investigate the effect of cardiac GRP78 gene transfer on Ca2+ dependent signaling, cell death, cardiac function and survival in clinically relevant in vitro and in vivo models for Dox cardiotoxicity.By using neonatal cardiomyocytes we could demonstrate that Dox induced Ca2+ dependent Ca2+ /calmodulin-dependent protein kinase II (CaMKII) activation is one of the factors involved in Dox cardiotoxicity by promoting apoptosis. Furthermore, we found that adeno-associated virus (AAV) mediated GRP78 overexpression partly protects neonatal cardiomyocytes from Dox induced cell death by modulating Ca2+ dependent pathways like the activation of CaMKII, phospholamban (PLN) and p53 accumulation. Most importantly, cardiac GRP78 gene therapy in mice treated with Dox revealed improved diastolic function (dP/dtmin) and survival after Dox treatment. In conclusion, our results demonstrate for the first time that Ca2+ dependent CaMKII activation fosters Dox cardiomyopathy and provide additional insight into possible mechanisms by which GRP78 overexpression protects cardiomyocytes from Doxorubicin toxicity.
Gesehen am 27.05.2019